Aesthetics is the Philosophy of Our Wordless World - Sue Spaid (Aesthetic Investigations, 2015)
For too long, philosophers have tried to force our world to comport to the ‘linguistic turn,’ made famous by Richard Rorty’s 1967 anthology of the same name. And as time marches on, we seem to have even fewer tools at our disposal to carve out alternative views, even though philosophers as varied as Gilbert Ryle and Maurice Merleau-Ponty once discerned our world quite differently. Aesthetics remains the philosophical field where language need not occupy center court. For this reason, Aesthetics matters more than those Realists, who are prone to dismiss non-evidential views, might admit.